1996
DOI: 10.1111/j.1476-5381.1996.tb16011.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of nitric oxide in allergen‐induced airway hyperreactivity to contractile agonists after the early asthmatic reaction: an ex vivo study

Abstract: Using a guinea‐pig model of allergic asthma, we investigated the role of nitric oxide (NO) in allergen‐induced airway hyperreactivity after the early asthmatic reaction, by examining the effects of the NO‐synthase inhibitor Nω‐nitro‐L‐arginine methyl ester (L‐NAME) on the responsiveness to methacholine and histamine of isolated perfused tracheae from unchallenged (control) animals and from animals 6 h after ovalbumin challenge. All animals developed airway hyperreactivity to inhaled histamine at 6 h after oval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
83
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 40 publications
11
83
2
2
Order By: Relevance
“…Indeed, both in vivo and ex vivo studies using the same species indicate that a deficiency of both epithelial and neuronal cNOS-derived NO underlies the development of AHR following the allergen-induced early asthmatic reaction ( fig. 1) [77,96,97]. A deficiency of cNOS activity and endogenous bronchodilating NO contributing to AHR was also demonstrated after repeated allergen challenge of sensitised guinea pigs [98,99].…”
Section: Acute Modulation Of Ahrmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, both in vivo and ex vivo studies using the same species indicate that a deficiency of both epithelial and neuronal cNOS-derived NO underlies the development of AHR following the allergen-induced early asthmatic reaction ( fig. 1) [77,96,97]. A deficiency of cNOS activity and endogenous bronchodilating NO contributing to AHR was also demonstrated after repeated allergen challenge of sensitised guinea pigs [98,99].…”
Section: Acute Modulation Of Ahrmentioning
confidence: 93%
“…In the respiratory tract, isoforms of constitutive NO synthase (NOS; cNOS) are mainly expressed in iNANC neurons (neuronal NOS (nNOS)), the endothelium (endothelial NOS (eNOS)) and the epithelium (nNOS and eNOS), which are primarily involved in the regulation of airway and vascular smooth muscle tone [76][77][78]. Moreover, eNOS-derived NO has been shown to inhibit airway inflammation by suppressing the activation of nuclear factor-kB, thereby inhibiting the expression of inducible NOS (iNOS), as well as the production of inflammatory cytokines [79][80][81][82].…”
Section: Acute Modulation Of Ahrmentioning
confidence: 99%
“…Pulmonary iNOS has been described in endothelial and epithelial cells and in macrophages of inflamed airways, and its induction results in the production of high (micromolar) levels of NO. However, BOER et al [14] suggested that contractile agonists, such as histamine, enhanced the production of constitutive NOS (cNOS), and not iNOS. cNOS, in the airways, is basally expressed in neuronal, endothelial and epithelial cells and its activation is dependent on an agonist-or depolarization-induced increase in intracellular Ca 2+ concentration, causing the production of small (picomolar) amounts of NO.…”
Section: Discussionmentioning
confidence: 99%
“…The preparations were attached to a perfusion holder and placed in an organ bath (37u) containing 20 mL gassed KH solution (extraluminal compartment) as described previously [17]. The tracheal lumen was perfused with recirculating KH solution from a separate 20-mL bath (intraluminal compartment) at constant flow rate, and hydrostatic pressure was measured at the proximal and distal ends of the trachea using axially centred side-hole catheters.…”
Section: Tracheal Perfusionmentioning
confidence: 99%
“…Increased consumption of L-arginine by arginase contributes to the development of allergen-induced AHR in acute allergic asthma by limiting the bioavailability of L-arginine to nitric oxide synthase (NOS) isozymes [13][14][15], which hydrolyse the amino acid into nitric oxide and Lcitrulline. This leads to a deficiency of bronchodilating nitric oxide, and increased formation of the highly reactive proinflammatory and procontractile nitric oxide metabolite peroxynitrite, both of which underlie AHR in animal models of allergic asthma [13][14][15][16][17][18]. In a guinea pig model of allergic asthma, inhalation of the specific arginase inhibitor 2(S)-amino-6-boronohexanoic acid (ABH) acutely reversed allergeninduced AHR in vivo both after the early and late asthmatic reaction, to a similar extent as treatment with inhaled L-arginine [19].…”
mentioning
confidence: 99%